Planejamento e participação: o caso da Luos 2016 e do Fortaleza 2040 - Gois, Rodolfo Anderson Damasceno (2018)
In the context of Brazilian urban policy, there have been recurrent conflicts between reformist and strategic matrix plans. The first one based on redistributive ideals, aims to promote social justice, as well as to democratize the planning and the management of the cities; the second, in turn, understands the city as an opportunity for profitable businesses, implying a planning and management of business trends, consubstantiating the attraction of investments, flexibilization of the guidelines and limits imposed by normative planning and the predilection for major urban interventions. In Fortaleza, after approval of the Participative Master Plan in 2009, in which it is possible to recognize, even partially, elements of a reformist nature, the implementation of the strategic matrix is verified through the most recent planning processes such as the revision of the Law of Use and Land Occupation 2016 and Fortaleza 2040. The first process was led by SEUMA, which since 2015 has been focused on the regulation of instruments for induction of urban development and real estate valorization, the most prominent being the proposal of Zona Especial de Dinamização Urbanística e Socioeconômica - ZEDUS; the second was coordinated by IPLANFOR, which intends, through Fortaleza 2040, to create and implement a "mega plan" that will guide all actions of urban development policy and other sectoral projects and will indicate new urban development projects for Fortaleza in its main products: Plan Master Urban and Mobility. Were these processes comparable, conflicting and complementary? How do they suppress the ideals of reform? In this research, it was verified that LUOS, through urbanistic parameters more permissive to the constructive densification, opens space for the projects of Fortaleza 2040 to be established in the city. Thus, both instruments are linked to a strategic matrix, insofar as they indicate spaces more favorable to the flexibilization of urban rates and, consequently, to the implementation of specific projects that favor the private sector. All this to the detriment of reformist alternatives of urban planning, considered more territorially inclusive and promoting inclusion and social justice.